(untitled) (Progressive Agriculture, 2013)
A field study was conducted on the nature and extent of damage of corn earworm, Helicoverpa zea (Boddie) in two maize varieties viz. BARI Hybrid Bhutta-5 and BARI Bhutta-7. The larvae caused damage by feeding on the ear tip at silk stage and then to kernel, the larvae were mainly confined to the ear tip and excreted faecal matter. It was found that the cob infestation rate was in linear progress and the mean cob infestation was 6.50% and 6.69% in BARI Hybrid Bhutta-5 and BARI Bhutta-7, respectively. The mean length of cob infestation was 24.90% and 25.07% and the mean number of kernel damage was 24.30 and 25.43 in BARI Hybrid Bhutta-5 and BARI Bhutta-7, respectively. The average yield loss was 0.016 t/ha in BARI Hybrid Bhutta-5 and 0.017 t/ha in BARI Bhutta-7. It was revealed from the results that BARI Bhutta-7 was more susceptible to this pest. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16849 Progress. Agric. 20(1 & 2): 49 55, 2009